2022
DOI: 10.1175/jhm-d-22-0011.1
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Standardized Drought and Flood Potential Index Based on Reconstructed Daily GRACE Data

Abstract: Multiple indicators derived from the Gravity Recovery and Climate Experiment (GRACE) satellite have been used in monitoring floods and droughts. However, these measures are constrained by the relatively short time span (∼20 years) and coarse temporal resolution (1 month) of the GRACE and GRACE Follow-On missions, and the inherent decay mechanism of the land surface system has not been considered. Here we reconstructed the daily GRACE-like terrestrial water storage anomaly (TWSA) in the Yangtze River basin (YRB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…A statistic or dynamic downscaling algorithm produced high spatial resolution GWS changes from the GRACE data [38,39]. A high spatial resolution GWS or a groundwater level map was produced by utilizing the relationship between TWS and hydro-climatic variables using machine learning, e.g., a regression tree [17,33]. To increase the model performance, we will consider machine learning or deep learning approaches as data fusion models in the future.…”
Section: Fusion Of Grace and Groundwater Level Datamentioning
confidence: 99%
See 1 more Smart Citation
“…A statistic or dynamic downscaling algorithm produced high spatial resolution GWS changes from the GRACE data [38,39]. A high spatial resolution GWS or a groundwater level map was produced by utilizing the relationship between TWS and hydro-climatic variables using machine learning, e.g., a regression tree [17,33]. To increase the model performance, we will consider machine learning or deep learning approaches as data fusion models in the future.…”
Section: Fusion Of Grace and Groundwater Level Datamentioning
confidence: 99%
“…Limited groundwater level in the long-term and dense measurements serve as quantitative indicators of local groundwater change, so that a high spatiotemporal resolution groundwater level cannot be acquired easily [4]. Groundwater level data can be reconstructed using machine learning methods based on simulation models and GRACE data [17]. Groundwater data are temporally sparse in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…Recent developments in GRACE data processing (Kvas et al, 2019) have enabled the computation of daily gravity fields with increased accuracy. Such daily gravity data were successfully used to study highfrequency, wind-driven sea level changes (Bonin and Chambers, 2011), short-term transport variations in the Antarctic Circumpolar Current (Bergmann and Dobslaw, 2012), the characteristics of major flood events (Gouweleeuw et al, 2018), high-frequency atmospheric fluxes (Eicker et al, 2020), and to analyze the development and propagation of water extremes by using a standardized drought and flood potential index (SDFPI; Xiong et al, 2022). Furthermore, the daily gravity-based TWS data appear particularly promising for capturing SM variations at short timescales but have not been used for this purpose yet.…”
Section: Introductionmentioning
confidence: 99%
“…Han et al [16] estimated the daily time series of water storage change in Bangladesh by inverting line-of-sight gravity difference (LGD) between two GRACE-FO spacecraft, which indicated that the daily LGD data can capture rapid water mass change at a sub-monthly time scale. A standardized flood potential index based on ITSG−Grace2018 daily solution was proposed by Xiong et al [17] and successfully detected 22 sub-monthly exceptional floods and droughts in the YRB between 1961 and 2015. As for the 2020 catastrophic flood in the YRB, Wang et al [18] combined GRACE data and the high-frequency ground gravity observations of gPhone to characterize 2020 flood events in YRB.…”
Section: Introductionmentioning
confidence: 99%